Precise determination of the total nitrogen content in activated sludge by ultrasonic pre-treatment assisted wet method - Zeng, Shangjing (Environmental technology, 2024)
The study proposed a method for determining total nitrogen (TN) content in activated sludge by ultrasound pre-treatment assisted wet method. Based on the single-factor experiment, with the TN content as the response value, the response surface methodology was employed to examine the individual and interactive effects of three factors: the dilution multiple of the sludge mixture, ultrasonic time, and ultrasonic power. At the same time, the physico-chemical parameters and the digestion-oxidation parameters were optimised. The results indicated that the optimal parameters were as follows; sludge dilution multiple of 225 times, stirring rate of 400 r/min, ultrasonic time of 22 minutes, ultrasonic power of 720 W, and optimal added volume of potassium persulfate at 8 mL with a digestion time of 40 minutes. The relative standard deviation (RSD) for the parallel determination of TN in sludge samples using ultrasonic pre-treatment assisted wet method was ≤2.77%, with a spike recovery rate of 98.49-101.43%. The method, ultrasonic pre-treatment assisted wet method to determine TN concentration in activated sludge, was simpler to operate, more accurate